Mecanismo gerencial para redução de atividades que consomem recursos, mas não agregam valor em obras de paredes de concreto - Torres, Taiane Aparecida Santos (2024)
The easing of real estate credit has propelled the construction industry forward. However, losses still plague the sector, a situation compounded by fierce competition among construction companies, leading them to seek new mechanisms that address a landscape with fewer losses and offer better competitive advantages. Among these methods is the adoption of lean construction, which, through lean practices such as best practices and facilitating activities, has supported the continuity of processes, reducing losses. Additionally, the trend towards more rationalized systems has emerged in the current market and has been integrated into lean principles to minimize non-value-adding activities on construction sites. It is noted that many studies have been conducted on losses in the sector, but in a very piecemeal manner, lacking a mechanism that can comprehensively address the issues raised. Therefore, this research sought to establish a managerial mechanism for the explicit delineation of lean best practices and/or facilitating activities, to reduce resource-consuming activities that do not add value to concrete wall construction projects. A multiple case study was conducted to validate the findings. The steps governing the consolidation of the research began with mapping the construction systems used in the municipality of Aracaju, followed by determining the maturity level in the on-site cast-in-place concrete wall construction system, defining the priority process, grouping lean practices in a database, and applying a game. The initial stage indicated an advancement of the rationalized system in the municipality, with 16 out of 20 surveyed projects employing the system. Questionnaires administered to construction management specialists, and those with a better understanding and mastery of the construction process, revealed a high maturity level in the PCML system, nearing maturity. Three construction processes were determined as priorities—formwork assembly, concreting, and reinforcement—for which the use of lean practices was proposed to eliminate non-value-adding activities. Site visits revealed that the major contributing factor to the occurrence of such activities in the analyzed projects was equipment and tools, with rework having the greatest impact. The non-utilization or inefficient utilization of facilitating activities for work inspection, preparation, and design were identified as solutions that should be implemented to avoid the identified losses. Through the application of the game, it was possible to detect weak points in the process that may be more susceptible to workflow disruptions. A means for controlling losses in priority processes was suggested, and a closer relationship between academia and the construction industry was proposed to ensure the efficiency fostered by the changes that have occurred in the sector over the years.